Secondary education for youths and adults in Argentina, Brazil and Chile during the period 2010-2023 - Olivares, Julián (2026)
This article aims to compare the development of secondary education for youths and adults in Argentina, Brazil and Chile between 2010 and 2023. To this end, adopt a quantitative approach and examine a set of statistical indicators related to: (a) the potential demand among youth and adult population to complete secondary education; (b) the evolution of specific school proposals designed to meet to this demand; and (c) their relevance within national educational systems.The analysis shows that, in all three countries, secondary education programs for youths and adults have performed a relatively similar role.